Solve for m
m=1
m=8
Share
Copied to clipboard
m^{2}-9m=-8
Subtract 9m from both sides.
m^{2}-9m+8=0
Add 8 to both sides.
a+b=-9 ab=8
To solve the equation, factor m^{2}-9m+8 using formula m^{2}+\left(a+b\right)m+ab=\left(m+a\right)\left(m+b\right). To find a and b, set up a system to be solved.
-1,-8 -2,-4
Since ab is positive, a and b have the same sign. Since a+b is negative, a and b are both negative. List all such integer pairs that give product 8.
-1-8=-9 -2-4=-6
Calculate the sum for each pair.
a=-8 b=-1
The solution is the pair that gives sum -9.
\left(m-8\right)\left(m-1\right)
Rewrite factored expression \left(m+a\right)\left(m+b\right) using the obtained values.
m=8 m=1
To find equation solutions, solve m-8=0 and m-1=0.
m^{2}-9m=-8
Subtract 9m from both sides.
m^{2}-9m+8=0
Add 8 to both sides.
a+b=-9 ab=1\times 8=8
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as m^{2}+am+bm+8. To find a and b, set up a system to be solved.
-1,-8 -2,-4
Since ab is positive, a and b have the same sign. Since a+b is negative, a and b are both negative. List all such integer pairs that give product 8.
-1-8=-9 -2-4=-6
Calculate the sum for each pair.
a=-8 b=-1
The solution is the pair that gives sum -9.
\left(m^{2}-8m\right)+\left(-m+8\right)
Rewrite m^{2}-9m+8 as \left(m^{2}-8m\right)+\left(-m+8\right).
m\left(m-8\right)-\left(m-8\right)
Factor out m in the first and -1 in the second group.
\left(m-8\right)\left(m-1\right)
Factor out common term m-8 by using distributive property.
m=8 m=1
To find equation solutions, solve m-8=0 and m-1=0.
m^{2}-9m=-8
Subtract 9m from both sides.
m^{2}-9m+8=0
Add 8 to both sides.
m=\frac{-\left(-9\right)±\sqrt{\left(-9\right)^{2}-4\times 8}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, -9 for b, and 8 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
m=\frac{-\left(-9\right)±\sqrt{81-4\times 8}}{2}
Square -9.
m=\frac{-\left(-9\right)±\sqrt{81-32}}{2}
Multiply -4 times 8.
m=\frac{-\left(-9\right)±\sqrt{49}}{2}
Add 81 to -32.
m=\frac{-\left(-9\right)±7}{2}
Take the square root of 49.
m=\frac{9±7}{2}
The opposite of -9 is 9.
m=\frac{16}{2}
Now solve the equation m=\frac{9±7}{2} when ± is plus. Add 9 to 7.
m=8
Divide 16 by 2.
m=\frac{2}{2}
Now solve the equation m=\frac{9±7}{2} when ± is minus. Subtract 7 from 9.
m=1
Divide 2 by 2.
m=8 m=1
The equation is now solved.
m^{2}-9m=-8
Subtract 9m from both sides.
m^{2}-9m+\left(-\frac{9}{2}\right)^{2}=-8+\left(-\frac{9}{2}\right)^{2}
Divide -9, the coefficient of the x term, by 2 to get -\frac{9}{2}. Then add the square of -\frac{9}{2} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
m^{2}-9m+\frac{81}{4}=-8+\frac{81}{4}
Square -\frac{9}{2} by squaring both the numerator and the denominator of the fraction.
m^{2}-9m+\frac{81}{4}=\frac{49}{4}
Add -8 to \frac{81}{4}.
\left(m-\frac{9}{2}\right)^{2}=\frac{49}{4}
Factor m^{2}-9m+\frac{81}{4}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(m-\frac{9}{2}\right)^{2}}=\sqrt{\frac{49}{4}}
Take the square root of both sides of the equation.
m-\frac{9}{2}=\frac{7}{2} m-\frac{9}{2}=-\frac{7}{2}
Simplify.
m=8 m=1
Add \frac{9}{2} to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}